Surgical Approach to Anterior Mediastinal Masses - Muharrem Özkaya; Nilay Çavuşoğlu (Acta Medica Alanya, 2019)
Aim: The aim of this study was to evaluate the clinical progress, type of surgical approach and early results of resection of anterior mediastinal masses. Patients and Methods: We retrospectively reviewed the reports of 25 patients who underwent surgery for an anterior mediastinal mass between 2014 and 2019. Patients’ age, gender, presenting symptoms, preoperative radiological investigations and surgical techniques were recorded. There were eight male and 17 female patients, and their age ranged from 18-89 with a mean of 44.4± 16.9 years. Results: The most frequent presenting symptoms were chest pain (90%) and cough (50%). The most common pathological diagnoses were thymic tumors (n=14, 56%) and lymphoma (n=5, 20%). Surgical approaches applied were median sternotomy in 16 patients, partial sternotomy in five patients and VATS (Video Assisted Thoracic Surgery) in four patients. There were no postoperative deaths or major complications, but eight patients had minor complications. Postoperative stay was 5±5.2 days.